2012
DOI: 10.1097/mcg.0b013e31824fff94
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Small-bowel Capsule Endoscopy Reading by Using Quickview Mode

Abstract: Quickview mode can reduce reading time but has an unacceptably miss rate for potentially important lesions. Use of a trained nonphysician assistant can reduce physician's time and improve diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…It was previously reported that interpretation of CE imaging requires a considerable amount of time, placing a significant burden on the reader 3 4 . There are also reports that described reading of CE images by health professionals other than gastroenterologists/endoscopists, e. g., nurses 5 6 7 8 9 . In this regard, improvements in the CE system should reduce the burden on the reader, with improvement in reading efficiency based on improvements in the software algorithm 3 9 10 11 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that interpretation of CE imaging requires a considerable amount of time, placing a significant burden on the reader 3 4 . There are also reports that described reading of CE images by health professionals other than gastroenterologists/endoscopists, e. g., nurses 5 6 7 8 9 . In this regard, improvements in the CE system should reduce the burden on the reader, with improvement in reading efficiency based on improvements in the software algorithm 3 9 10 11 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The role played by other health professionals "pre-readers," such as nurses, in interpretation of CE has been discussed in Europe and the United States 6 7 11 16 . It has been reported that non-physician assistants can contribute toward shortening the reading time and improving the diagnostic ability of physicians 6 7 . Therefore, new approaches, such as examination of the learning curve, training, and certification system, have been reported 11 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that training with at least 50 evaluations is required for achieving a very high accuracy in VCE pre-reading by nurses. Of note, some studies found that an expert nurse (60 VCE procedures) was equally accurate as the expert physician (250 VCE procedures) and more accurate than physicians with 100 VCE procedures experience, irrespective of the software used [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Images are filtered according to a specific algorithm developed by the manufacturer, and sampling rates between 2% and 80% can be chosen. Shiotani et al examined how different sampling rates affect the detection rates of quick view CE [ 80 ]. A variety of preselected lesions were included in the study.…”
Section: Reading Protocolsmentioning
confidence: 99%